2022
DOI: 10.3389/fbioe.2022.898240
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Gastric Cancer Activity of the Cell-free Culture Supernatant of Serofluid Dish and Lactiplantibacillus plantarum YT013

Abstract: Graphical AbstractThe overall mechanisms for the induction of apoptosis in AGS cells by the CCS2 prepared from the selected L. plantarum YT013 were summarized as the picture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In another study, L. buchneri FD2 showed selectivity in killing cancer cells compared to the WRL68 normal liver cell line. In addition, research has shown that Lactiplantibacillus plantarum YT013 and the cell-free culture supernatant from serofluid dish could inhibit the proliferation of the cancer cell lines without causing harm to healthy cells 62 .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, L. buchneri FD2 showed selectivity in killing cancer cells compared to the WRL68 normal liver cell line. In addition, research has shown that Lactiplantibacillus plantarum YT013 and the cell-free culture supernatant from serofluid dish could inhibit the proliferation of the cancer cell lines without causing harm to healthy cells 62 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Enterococcus faecalis has been shown to induce the production of intracellular reactive oxygen species through an oxidative phosphorylation‐independent pathway, resulting in restraint of DNA damage repair and downregulation of cell cycle regulation genes 26 . Another example is Lactiplantibacillus plantarum YT013 , which was reported to inhibit GC cell proliferation and promote cell apoptosis through endogenous mitochondrial apoptosis pathways 27 . In this study, we focus on reporting the role of P. intermedia derived from GC tissues, which appears to promote cell proliferation, migration, and invasion in GC.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Another example is Lactiplantibacillus plantarum YT013 , which was reported to inhibit GC cell proliferation and promote cell apoptosis through endogenous mitochondrial apoptosis pathways. 27 In this study, we focus on reporting the role of P. intermedia derived from GC tissues, which appears to promote cell proliferation, migration, and invasion in GC. These findings contribute to the growing understanding of the potential effect of microbial species on cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that 5-FU is the most used chemotherapeutic agent in colorectal cancer treatment. It has been approved that Uro-A is able to sensitize colon cancer cells to 5-FU (Zhang et al, 2022).…”
Section: Chemo-sensitizing Agents Derived From Micro-organism Sourcesmentioning
confidence: 99%